Security Analysis of Mobile Edge Computing in Virtualized Small Cell Networks - Vassilakis, Vassilios; Chochliouros, Ioannis P.; Spiliopoulou, Anastasia S.; Turyagyenda, Charles; Dardamanis, Athanassios (Springer International Publishing., 2016)
Based upon the context of Mobile Edge Computing (MEC) actual research and within the innovative scope of the SESAME EU-funded research project, we propose and assess a framework for security analysis applied in virtualised Small Cell Networks, with the aim of further extending MEC in the broader 5G environment. More specifically, by applying the fundamental concepts of the SESAME original architecture that aims at providing enhanced multi-tenant MEC services through Small Cells coordination and virtualization, we focus on a realistic 5G-oriented scenario enabling the provision of large multi-tenant enterprise services by using MEC. Then we evaluate several security issues by using a formal methodology, known as the Secure Tropos.
Keywords: Virtual Network Function (VNF); Small Cell (SC); Software Defined Networking (SDN); Network Functions Virtualization (NFV)